2012
DOI: 10.1103/physrevb.86.035115
|View full text |Cite
|
Sign up to set email alerts
|

Role of band structure and local-field effects in the low-energy collective electronic excitation spectra of 2H-NbSe2

Abstract: We present a study of the electron dynamics in the layered compound 2H -NbSe 2 . First-principles calculations are used to obtain the band structure employed in the evaluation of the loss function with inclusion of local-field (LF) effects. Two different symmetry directions [(100) and (010)] were explored in the hexagonal basal plane. In both cases, a low-energy charge-carrier plasmon (CCP) at ∼1 eV presenting a negative dispersion over a wide momentum transfer range is found, in agreement with recent experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 66 publications
2
45
2
Order By: Relevance
“…2 we compare the low-energy (0-4 eV) EELS spectra of 1T-VSe 2 and 1T-TiTe 2 with that of 2H-NbSe 2 calculated in RPA for momentum transfers q along M, i.e., belonging to the plane of the layer. While in 2H-NbSe 2 (and similarly for the other metallic compounds of the 2H family [19][20][21]) the loss function at small q is dominated by a single sharp peak at ∼1 eV, in the 1T materials it is strongly broadened with two main features (at ∼0.6 and 1.7 eV) and several other minor structures involving independent electron-hole pairs. Moreover, while in the 2H polytypes the sharp peak has a negative dispersion as q increases [19][20][21], in 1T-VSe 2 and 1T-TiTe 2 the lowerand higher-energy excitations have positive and negative dispersion, respectively.…”
Section: A In-plane Loss Functionmentioning
confidence: 98%
See 2 more Smart Citations
“…2 we compare the low-energy (0-4 eV) EELS spectra of 1T-VSe 2 and 1T-TiTe 2 with that of 2H-NbSe 2 calculated in RPA for momentum transfers q along M, i.e., belonging to the plane of the layer. While in 2H-NbSe 2 (and similarly for the other metallic compounds of the 2H family [19][20][21]) the loss function at small q is dominated by a single sharp peak at ∼1 eV, in the 1T materials it is strongly broadened with two main features (at ∼0.6 and 1.7 eV) and several other minor structures involving independent electron-hole pairs. Moreover, while in the 2H polytypes the sharp peak has a negative dispersion as q increases [19][20][21], in 1T-VSe 2 and 1T-TiTe 2 the lowerand higher-energy excitations have positive and negative dispersion, respectively.…”
Section: A In-plane Loss Functionmentioning
confidence: 98%
“…Since in our preliminary tests we found that in the small-energy range considered here the effect of f xc in the adiabatic local-density approximation is negligible (see also Refs. [20] and [21]), in the following we will consider results obtained in the random-phase approximation (RPA) in which f xc = 0 and that has already been proven to be sufficient to obtain a good agreement with available experimental data [18,19,22]. This approximation has been used to evaluate the loss function of single-sheet TMD as well since previous works on graphene and single-wall carbon nanotubes, see e.g.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallic TMDCs have much higher charge carrier densities leading to plasmon energies of around 1 eV in bulk TMDCs. [12][13][14][15] Together with the possibility of tuning the plasmon energies and lifetimes through quantum confinement or plasmon hybridization, 16,17 this makes few-layer TMDCs interesting candidates for nanoplasmonic applications in the optical frequency regime. We mention that the efficient coupling of 2D plasmons and light generally requires some kind of scattering of the light to overcome the momentum mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for both metals and insulators, it is possible to identify two plasmons in the EELS spectra measured for in-plane momentum transfer: a low-energy plasmon at about 9 eV and a high-energy plasmon involving all valence electrons at about 23 eV. Beside these two features, metallic TMD present also an intraband plasmon at about 1 eV involving only the charge-carrier electrons [17][18][19][20]. However, neutral excitations in these materials have never been studied at large momentum transfer where the short-range part of the Coulomb interaction plays a key role.…”
Section: Introductionmentioning
confidence: 96%